Analysis of Engineering students' errors and misunderstandings of integration methods during the COVID-19 - Fateme Moradi; Zahra Rahimi; Zohreh Nekouee (Universidad de Deusto, 2023)
The prevalence of the COVID-19 pandemic and its consequences, such as the closure of educational centers and the requirement to use virtual education, have all challenged students' learning. Students' mathematical misunderstandings can be regarded as one such challenge. While such problems may also occur in face-to-face training, where teachers and educators are involved, it seems that this problem is more serious in virtual education. The purpose of the present study was to investigate students' misunderstandings in regard to integration methods. More specifically, the statistical population of this study consisted of engineering students from Islamic Azad University. The sample members included 40 students from the faculty of engineering who had been taught Mathematics1 by virtual education in the first semester of the academic year 2021-2022. To conduct this research, students were taught different methods of integration in cyberspace for six consecutive weeks. During these six stages, tests were conducted online to assess students. The results showed that most of the students' errors were conceptual and computational in nature; they were rooted in no suitable understanding of the basic concepts of mathematics and the lack of good education in high school. Received: 3 May 2022 Accepted: 15 April 2023